1974
DOI: 10.1104/pp.54.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cadmium Uptake by Plant Tissue

Abstract: Since it is now well demonstrated that Ca is required to maintain the structural and functional integrity of plant cell membranes (1,2,12,14,18), Ca was included at 0.2 mm in all experimental solutions. The pH of absorption solutions, initially 5.5, did not vary by more than 0.2 units during the experiments. The absorption period, which varied from 2 to 120 min, was terminated by one of two methods, depending on whether or not that fraction of labeled Cd associated with the tissue in readily exchangeable form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
54
1
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(60 citation statements)
references
References 14 publications
3
54
1
2
Order By: Relevance
“…In studies with radiolabelled Cd, Cutler and Rains (1974) found that 79% of tracer accumulated by excised barley roots during a 30-min exposure to 9 × 10 -5 M 115 Cd could be desorbed by 4.5 × 10 -4 M unlabelled Cd. After exposure to 0.05-5.0 × 10 -6 M 109 Cd for 5 h, 41-48% of tracer was desorbed from spruce seedling roots by a 20-fold concentration of unlabelled Cd (Godbold 1991).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In studies with radiolabelled Cd, Cutler and Rains (1974) found that 79% of tracer accumulated by excised barley roots during a 30-min exposure to 9 × 10 -5 M 115 Cd could be desorbed by 4.5 × 10 -4 M unlabelled Cd. After exposure to 0.05-5.0 × 10 -6 M 109 Cd for 5 h, 41-48% of tracer was desorbed from spruce seedling roots by a 20-fold concentration of unlabelled Cd (Godbold 1991).…”
mentioning
confidence: 99%
“…Cutler and Rains (1974), working with 8.9 × 10 -6 M Cd in nutrient solution and excised barley roots, concluded that accumulation of Cd in barley tissue was a non-metabolic (passive) process, involving diffusion coupled with sequestration. However, 8.9 × 10 -6 M Cd is a high, probably phytotoxic, level of Cd exposure, and the conclusion that Cd uptake was a passive process (Cutler and Rains 1974) should not be applied to lower, more environmentally relevant concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of cadmium by roots and its transport to the upper part of plants is a very fast process. Cd content in barley tissues can excess Cd concentration in soil after longer exposure (Cutler and Rians 1974). The rapid Cd accumulation in plants became crucial agricultural problem all over the world causing a reduction in crop growth and productivity, but it has also several consequences to human health.…”
mentioning
confidence: 99%
“…8). The mechanism of Cd uptake to the plant root is exchange absorption, diffusion and irreversible binding [22]. This is due to the large negative electric potential existing at the exterior surface of the root plasma membrane, provides enough energy to drive the uptake of Cd 2+ [6].…”
Section: Metal Accumulation In the Plant Rootmentioning
confidence: 99%